2003
DOI: 10.1113/eph8802511
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Cytoskeleton in Intracellular Arrangement and Regulation of Mitochondria

Abstract: It is a well-known phenomenon that in permeabilized oxidative muscle cells the apparent K m for exogenous ADP in the control of mitochondrial respiration is very high, in the range of 250-350 mM, in contrast with isolated mitochondria in vitro (where the apparent K m for ADP is 15-20 mM: Kummel 1988;Saks et al. 1991Saks et al. , 1993Saks et al. , 1994Saks et al. , 1995Saks et al. , 1998bSaks et al. , 2001Fontaine et al. 1995;Veksler et al. 1995;Kuznetsov et al. 1996; Kay et al. 1997a,b,c;Milner et al. 2000;Anf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 37 publications
6
91
1
8
Order By: Relevance
“…It has been suggested that the sensitivity of muscle mitochondria to cytosolic ADP depends on the cytoarchitecture and cytoskeleton (1). Because the apparent K m for cytosolic ADP increased in CK Ϫ/Ϫ gastrocnemius muscle in parallel with increased crowding of mitochondria as demonstrated in this study, it is tempting to speculate that high K m for ADP in oxidative muscles is simply a direct consequence of mitochondria being crowded within clusters, leading to decreased access of cytosolic ADP to the mitochondrial surface.…”
Section: Possible Physiological Implicationsmentioning
confidence: 48%
“…It has been suggested that the sensitivity of muscle mitochondria to cytosolic ADP depends on the cytoarchitecture and cytoskeleton (1). Because the apparent K m for cytosolic ADP increased in CK Ϫ/Ϫ gastrocnemius muscle in parallel with increased crowding of mitochondria as demonstrated in this study, it is tempting to speculate that high K m for ADP in oxidative muscles is simply a direct consequence of mitochondria being crowded within clusters, leading to decreased access of cytosolic ADP to the mitochondrial surface.…”
Section: Possible Physiological Implicationsmentioning
confidence: 48%
“…In isolated mitochondria, respiration is characterized by an apparent K m for exogenous ADP that is about 10-fold lower than in permeabilized cells with oxidative metabolism (Appaix et al 2003;Saks et al 1995). In other words, in permeabilized cells with oxidative metabolism ANT is less accessible to cytosolic ADP than in isolated mitochondria.…”
Section: Vdac Regulation By Tubulinmentioning
confidence: 99%
“…In other words, in permeabilized cells with oxidative metabolism ANT is less accessible to cytosolic ADP than in isolated mitochondria. Saks and coauthors (Appaix et al 2003) have found that mild trypsin treatment of permeabilized cardiomyocytes and cardiac fibers resulted in a decrease in apparent K m for ADP, or an increase of MOM permeability up to the level of the high MOM permeability of isolated mitochondria. They also observed that this processes is accompanied by disintegration of the mitochondrial network, which otherwise is very structured in cardiac cells, and by rearrangement of the microtubule network (Appaix et al 2003).…”
Section: Vdac Regulation By Tubulinmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effects have been studied on the localization and function of mitochondria. Structural studies of intracellular arrangements of mitochondria into functional complexes with myofibrils and sarcoplasmic reticulum demonstrate their importance in mitochondrial oxydative activity and membrane permeability (Andrienko et al, 2003;Appaix et al, 2003). There are findings with pathological respiratory chain enzyme activities in patients with MFM (Reimann et al, 2003).…”
Section: Energy Metabolismmentioning
confidence: 90%